KOLABORASI MASYARAKAT SIPIL, POLITIK DAN EKONOMI DALAM PEMANFAATAN MODAL SOSIAL (KASUS PELESTARIAN LINGKUNGAN PESISIR PADA MASYARAKAT BALI AGA- DESA LES BALI UTARA) - I Wayan Mudana (Environmental Research Center (PPLH) of Udayana University, 2013)
AbstractThis research aims to understand the back ground the collaboration of civil community,politic and economic in presenting social capital, shape of ideal text and social capital textthat is presented and process social process, and so controlling of sociality that’s carriedout in guiding to the beach environment conservation at Les Bali Age, North Bali.This research using qualitative approach, informant is determined by snowball purposivesystem, collecting data is done with interviewing, observation, document method, whiledata analyze is carried out through triangulation, which is going on with interpretationprocess. According to that problem is known that collaboration of civil community, politicand economic to present the social capital in beach circles collaboration at Les villagecommunity is based on awareness to environment and its resources that has the value tocivil community, economic and politic. In that framework some kind of social capital thatbelongs to local community in the system of cultural value, institution, activity pattern andphysical culture have been used in optimal manner.The shape of ideal text and social text of social capital that’s presented by civil community,economic and politic, there is Tri Hita Karana ideology, Nyegara gunung ideology,development which has environment perception, with clear beach and still in eternalcondition, awig-awig agreement, family group/dadia, fisherman group, pecalang segara(sea guider), Pokmaswas, strengthen the similarity, help each others and also believe eachothers among community members, while the physical culture that’s developed are; beachsupport, technology development of ridge of rock, technology development of fish catchingthat’s clever around environment. Investment of social capital is started by socializationprocess, the strength of social trust to the idea of beach circles eternity, by involving theLSM, village apparatus, figure of local community, and continued with developing thefisherman group, who’s catching the goldfish and circles eternity, pecalang and making theregulation. The social control mechanism that’s carried out, has their characteristic fromhigh level and low level, sekala and niskala character, started by socialism process that’scontinued by LSM, water police, Pokmaswas, village apparatus, pecalang, and locanfisherman group